Geotecnologia aplicada à sub-bacia hidrográfica do Rio Piauitinga e suas relações ambientais - Moreira, Flávia Dantas (2008)
The complexity and challenges of using the sub-basin of the river Piauitinga were approached from the choice of methodology geosystem suited for small river basins based on diagnosis of geoenvironmental and socioeconomic conditions. The area under study includes the municipalities Lagarto, Boquim, Salgado and Estancia and making the area of 411.98 square km and a length of 59.86 km main river, contributing to the water supply of about 120,000 people through two points of abstraction , The top course by the Integrated System Piauitinga - Salgado and low going through the SAAE - Estancia. Thus, there were conceptual and theoretical discussions concerning the geographical concepts, geomorphologic, theory of systems, geoprocessing, allowing a geographical analysis of the occupation of the sub-basin of the river Piauitinga. As for results, involved the analysis of constraints geoenvironmental characterized by the increased presence of the Group Board Coastal Barriers associated with a magnitude of altimetry 184m, with half its area consists of flat areas, providing runoff slow, not requiring sophisticated practices for soil conservation, and the socioeconomic variables in line with the human interference in the modification of the landscape. The consequences of the use and occupation of land were made through the image of satellite SPOT 5 (2005), which was returned the bodies in the water scale 1: 25,000, increasing the quantity and quality of existing information, product whose previous date of the decade 1970 in the scale 1: 100,000, identifying channels 1724. The use and occupation of land left the area prior recognition of the field and in view of the image, constituting themselves into classes degraded area, the urban area, capon, forest, agricultural crops and pasture, associated with conditions of water bodies. Based on studies using this sub-basin, with important source for water supply, which currently comprises about 10% of the population of Sergipe, is threatened due to the actions impact sanitation, deforestation, removal of sand in bed and landfill. So, hold up measures mitigating they understand, implementation of sanitation, shares of replanting in water courses and top strand and effective actions of environmental education, systematized from the consolidation of unit manager - Committee, aimed at reducing conflicts use of natural resources in the sub-basin of the river Piauitinga.